Public Policies in Shared Societies A Comparative Approach - Fitzduff, Mari.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2013)
Communities throughout the world are increasingly diverse in their racial, ethnic and religious make up. Using examples drawn from over 50 countries in a variety of fields from economics to education, this book explores how governmental, economic and social institutions are adapting their policies to create more cohesive and peaceful societies.
Keywords: Political science; Comparative politics; Public policy; Public administration; Political sociology; Economic development; Political Science and International Relations; Political Science; Public Policy; Political Sociology; Development Studies; Comparative Politics; Public Administration